2020
DOI: 10.38076/ideijeb.v1i2.18
|View full text |Cite
|
Sign up to set email alerts
|

Keunggulan Bersaing Umkm Kuliner Berbasis Inovasi (Studi Pada Umkm Keripik Samiler Kasper Di Sidoarjo)

Abstract: This research was conducted in Sidoarjo, namely in the "Kasper" Samiler Crackers business which aimed to determine the innovation strategy and competitive advantage of the Kasper Samiler Crackers. This research was a research that used a qualitative approach. Which used interview and observation instruments. Data collection techniques used were observation, interview, documentation and triangulation techniques. The results showed that the innovations made by Samiler Casper Crackers were innovations in products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…To become a leader in it, you need to develop an objective marketing strategy as a top priority to combat competition and develop the market. With this background, it is important to analyze marketing strategies on competitive advantages by raising the title "Marketing Strategy Analysis on the Competitive Advantages of Culinary SMEs in Makassar City" because it can be concluded that good management and marketing strategies will increase competitiveness in the market so that they include advantages that can build competitive productivity (Siswati & Alfiansyah, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To become a leader in it, you need to develop an objective marketing strategy as a top priority to combat competition and develop the market. With this background, it is important to analyze marketing strategies on competitive advantages by raising the title "Marketing Strategy Analysis on the Competitive Advantages of Culinary SMEs in Makassar City" because it can be concluded that good management and marketing strategies will increase competitiveness in the market so that they include advantages that can build competitive productivity (Siswati & Alfiansyah, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Inovasi sangat dibutuhkan oleh UMKM untuk dapat bersaing serta menghasilkan produk-produk terbaru yang berbeda (Siswati & Alfiansyah, 2020), sehingga konsumen lebih tertarik membeli produk. Inovasi mencakup pembaharuan produk, penemuan jasa, dan inovasi proses (Dhewanto, Indradewa, Ulfah, Rahmawati, Yoshanti, & Lumanga, 2015).…”
unclassified